Comparison of bone SPECT/CT and MRI in detection of pain generator in ankle and foot pain: a retrospective diagnostic study. Issue 10 (1st June 2021) - Agrawal, Kanhaiyalal; Swaroop, Shakti; Patro, P. Sai Sradha; Tripathy, Sujit Kumar; Naik, Suprava; Velagada, Sandeep
Abstract : Objective: To study the sensitivity and specificity of MRI and bone SPECT-CT in detecting the pain generator in ankle and foot pain with diagnostic dilemma. Methods: Retrospectively data of patients with ankle or foot pain who underwent both MRI and Bone SPECT-CT were analyzed. The lesions and probable pain generator sites were reported as per MRI and bone SPECT-CT findings. These lesions were correlated clinically, managed accordingly and followed up. The patients who had significant improvement in response to the treatment provided were considered to have been diagnosed accurately. The foot and ankle disability index (FADI) was used to evaluate the patient's pre- and postintervention condition. Results: The study included 37 patients retrospectively (18 women and 19 men). The lesions were classified into soft tissue lesions (ligaments/tendons), joint lesions (arthritis) and bony lesions (fractures/osteomyelitis/osteochondral lesions). Overall, MRI had sensitivity, specificity, positive predictive value and negative predictive value of 82, 31, 74 and 42%, respectively, and SPECT-CT had sensitivity, specificity, positive predictive value and negative predictive value of 84, 60, 84 and 60%, respectively. The mean FADI score pretreatment for all patients was 61.5 (SD = 13.8) and posttreatment 88.4 (SD = 13.01) showing significant improvement in the score ( P < 0.05), suggesting that the final diagnosis of these patients was accurate. Overall, management change due to bone SPECT-CT over MRI was seen in 26% of patients. Conclusion: Bone SPECT-CT has incremental value over MRI in the diagnosis of pain generator in foot and ankle pain. The overall specificity of bone SPECT-CT is higher than MRI in detection of pain generators. Bone SPECT-CT performed better than MRI in detection of culprit pathology in the bone, whereas MRI is better in soft tissue lesions. Advances in knowledge: There are only a few published literature with direct comparison of bone SPECT-CT scintigraphy and MRI in detection of foot and ankle pain generator. This study directly compares diagnostic utility of bone SPECT-CT scintigraphy and MRI in foot and ankle pain. In the present study, the bone SPECT-CT performed better than MRI in detection of culprit pathology in the bone, whereas MRI is better in soft tissue lesions.